The Criminal Responsibility of the Offender in the Theft of Railway Iron Owned by PT. KAI Drive Natar (Case Study of Verdict No. 28/Pid.B/2024/PN.Kla) - Hartono, Bambang; Seftiniara, Intan Nurina; Hussein, Thendy (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research examines the criminal responsibility of the perpetrator in the case of theft of rail iron belonging to PT. KAI Drive Natar, as stated in Decision Number 28/Pid.B/2024/PN.Kla. The focus of the discussion is directed at the factors behind the theft and the forms of legal responsibility imposed on the perpetrators. This crime was committed by two defendants who misused official attributes to disguise their criminal actions, which resulted in a loss of IDR 18,000,000. This research uses a normative juridical method with a case study approach. The research results show that apart from economic factors and opportunities, weak supervision is one of the main triggers for this criminal act. From a legal aspect, the perpetrator's responsibility refers to the provisions of Article 362 and Article 363 of the Criminal Code which regulate theft by aggravation. In handing down a decision, the panel of judges considered the elements of the crime and the role of each defendant. It is hoped that this study will provide a deeper understanding of law enforcement practices and serve as material for evaluating the effectiveness of criminal sanctions in dealing with theft of state-owned assets.